ANALISIS DETERMINAN PERTUMBUHAN EKONOMI DI INDONESIA TAHUN 1992-2022 - Pramesty, Sherlinda Ardyana; Adianita, Happy (MediaTrend, 2023)
Economic growth is an issue that can have an impact on the welfare of a country. So the reason for this research aims to analyze the factors that influence economic growth in Indonesia for the 1992-2022 period. The use of the Error Correction Model (ECM) analysis method with the help of Eviews 12 was carried out to review the influence analysis on economic growth in Indonesia during the research period in the short and long term. Time series data used for this research from 1992-2022 were obtained from the Indonesian Central Statistics Agency (BPS). The economic growth indicator is used as the dependent variable, while the poverty level, labor force level, unemployment rate and APBN are independent variables. The results of empirical tests using Error Correction Model (ECM) analysis determine that short-term and long-term poverty levels have a significant positive influence on economic growth in Indonesia. At the labor force level it has no significant effect either in the short or long term. However, the unemployment rate variable has a significant positive effect in the long term but no significant effect in the short term. and Realization of state revenues in the APBN does not have a significant long-term or short-term effect on economic growth in Indonesia.